ANALISIS KEPATUHAN BENDAHARA DANA BOS SDN X TERHADAP ASPEK PERPAJAKAN (Jurnal Proaksi, 2022)
AbstractThe 2021 BOS funds have been distributed to the elementary school sub-sector are Rp. 23.8 trillion, but this has not been offset by tax revenues sourced from these funds. This study focuses on the level of tax obligations of treasurers of BOS funds. The purpose of this research is to analyze the obligations of the treasurer in the taxation aspect. This research is a qualitative exploratory research based on case study. This research findings is that the obligation to withhold and/or collect taxes as well as deposit and report taxes at SDN X has not been fully implemented in accordance with tax provisions. The conformity level of the implementation of the tax obligations of the Treasurer of SDN X against the tax provisions is 62.5%. This indicates that the BOS fund treasurer has not complied with his tax obligations. It is recommended that the KPP provide counseling and training on BOS fund treasurers.Keywords: Taxation, Compliance, Bos Fund Treasurer